Évolution des politiques environnementales et tourisme de montagne au Népal - Isabelle Sacareau (Revue de Géographie Alpine)
Against a backdrop of environmental crisis, attributed to the impact of tourism and the practices of rural populations, Nepal has created protected areas with a view to preserving the Himalayan environment and promoting sustainable tourism in the regions concerned. Given the conflicts between conservation needs and development needs, local communities are now being given a bigger role in the governance of these protected areas. Yet the measures being taken simply accompany and guide well-established tourism dynamics that operate on a much greater scale. Trekking is thus a tourism system largely in the hands of the country’s mountain communities and is an activity that has enabled these communities to improve their living conditions while at the same time limiting environmental impacts. In this sense it is very much in line with the principles of sustainable development.